Diferencia entre revisiones de «Teoría de placas y láminas»

<math>U=\|\mathbf{r}_\theta\| =R_C, \qquad
V=\|\mathbf{r}_\phi\| = R_C\sin\theta</math>
||left}}lef
Y por tanto las ecuaciones anteriores quedarán reducidas a:
{{ecuación|
<math>\begin{cases}
+n_{\phi\phi}\cos\theta + q_\theta - (n_{\theta\theta})'_\theta - n_{\theta\theta}\tan\theta = -R_Cp\sin\theta \\
-n_{\phi\theta}\cos\theta +\cfrac{q_\phi}{\sin\theta}- (n_{\theta\phi})'_\theta - n_{\theta\phi}\tan\theta = 0 \\
-n_{\theta\theta} - \cfrac{n_{\phi\phi}}{\sin\theta} -(q_\theta)'_\theta - q_\theta\tan\theta = -R_Cp\cos\theta \\
+m_{\phi\phi}\cos\theta + R_Cq_\theta -(m_{\theta\theta})'_\theta - m_{\theta\theta}\tan\theta = 0 \\
-m_{\phi\theta}\cos\theta + R_Cq_\phi -(m_{\theta\phi})'_\theta - m_{\theta\phi}\tan\theta = 0 \end{cases}</math>
||left}}
 
=== Lámina axisimétrica ===
Usuario anónimo